(untitled) (Journal of Contemporary Issues in Accounting, 2023)
The role audit committee traits play in promoting revenue growth of banks has been well established in developed economies; however, there seems to be a literature gap on what is known about this research theme in developing economy like Nigeria. Given the literature gap, this paper identified two (2) audit committee traits (audit committee diversity and meetings) and the roles they play in promoting revenue growth of publicly quoted commercial banks in Nigeria. Ex-post facto research design and secondary data were employed; data were obtained from audited financial statements of fifteen (15) commercial banks from 2011-2020. The panel data obtained was dissected using descriptive and inferential statistical tools. Specifically, the fixed and random effect panel data regression indicated that audit committee diversity positively significantly affects revenue growth of banks. Contrarily, we found a negative insignificant effect of audit committee meetings on banks’ revenue growth; this result corresponds with agency theory such that increased meetings of audit committee would lead to increased agency cost to bank. In line with the finding, we advocated decreased number of meetings of audit committee, since it has shown to negatively insignificantly affects banks’ revenue growth. On the other hand, diversity in the audit committee needs to accommodate the current and future multiplicity of members (male and female members), as well as increasing their numbers since it has shown to positively significantly affects banks’ revenue growth.